Observations on the use of attention markers in Comrac Líadaine ⁊ Chuirithir - Stifter, David (Studia Celtica Posnaniensia, 2024)
In a series of articles, Aaron Griffith (2008, 2010, 2011, 2013) and Bernhard Bauer (2018: 12-13) have shed light on the pragmatic function and the syntactic operation of the Old Irish notae augentes and the anaphoric pronoun suide/-side, which for practical purposes can be grouped together under the umbrella term ‘attention markers’. The comparatively high incidence of these elements in the late Old Irish tale Comrac Líadaine ⁊ Chuirithir ‘The Encounter of Líadain and Cuirithir’ (Stifter forthc.), provides an opportunity to test these hypotheses and to add to and refine the description of their syntactic and pragmatic functions. In addition to two previously established functions, namely 1. to direct the mental focus of the recipients and 2. to distinguish between overall and temporarily salient referents, two hitherto unrecognised usages of attention markers can be identified for Old Irish, namely 3. as argument-fillers after quotative verbs, and 4. as verbal gender-markers.